Dapagliflozin improves left ventricular myocardial longitudinal function in people with type 2 diabetes. (25th November 2020) - Brown, A.J.M; Gandy, S; McCrimmon, R; Struthers, A; Lang, C
Abstract: Background/Introduction: Asymptomatic left ventricular (LV) dysfunction is highly prevalent in patients with type 2 diabetes mellitus (T2DM). Sodium-glucose cotransporter 2 (SGLT2) inhibitors have been shown to reduce all-cause mortality and hospitalisations for heart failure in patients with T2DM. The underlying mechanisms for these cardiovascular benefits are unclear. In the Dapa-LVH trial, we had previously shown that dapagliflozin treatment significantly reduces LV mass (LVM) compared to placebo in patients with T2DM and LV hypertrophy (LVH). Purpose: The objective of this sub-study of the Dapa-LVH study was to assess whether dapagliflozin treatment improves LV myocardial longitudinal function and LV diastolic function in patients with T2DM and LVH. Methods: We randomly assigned 66 people (mean age 67±7 years, 38 males) with T2D, LVH with a normal LV ejection fraction to receive dapagliflozin 10mg once-daily or placebo for 12 months. The primary endpoints were change in global longitudinal strain (GLS) and LV diastolic function defined as the ratio of mitral inflow E to mitral e' annual velocities assessed using echocardiography. Secondary endpoints were left ventricular and atrial volumes assessed using cardiac magnetic resonance. Results: Dapagliflozin treatment resulted in a median increase in GLS of −1.64±2.5% vs placebo −0.2±1.8; p=0.024, with a mean difference of −1.4% (95% CI: −2.7 to −0.2). There was a trend towards a reduction left atrial area with a median change in left atrial area of the dapagliflozin group −0.5±3.75 cm 2 vs placebo group 0.0±3.5 cm 2 ; p=0.088), leading to an absolute mean difference of −1.29cm 2 (95% CI: −3.01 to 0.44). There was no significant difference between dapagliflozin and placebo in E/e' and in LV volumes. Conclusion: Dapagliflozin treatment improved LV myocardial longitudinal function which may suggests it may improve subclinical LV dysfunction. Funding Acknowledgement: Type of funding source: Private grant(s) and/or Sponsorship. Main funding source(s): This study was funded by an Externally Sponsored Research grant from Astra Zeneca – (grant number ESR-14-10168